UKRAINIAN POETRY OF 90TH XX: CONTEXT «NEW DEGENERATION» - Baran, Ye. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
Becoming of a new Ukrainian poetry at the beginning of 90th years ХХ of age through evolution of aesthetically beautiful and world view experience of literary groupment «New deґeneratsiya»(Stepan Protsyoc, Ivan Androusyac, Ivan Tsiperdyoc) is examined in the article.